INDUSTRI MEDIA BUDAYA POPULER ANALISIS SEMIOTIKA PEIRCE PADA DRAMA KOREA START UP - Bimantoro, Anggana Aletta; Sary, Marisa Puspita; Putri, Rizki Anindia (Universitas Teuku Umar, 2021)
The focus of this studied lies in understanding the meaning behind the 'start up' Korean drama scene. The purpose of this study was to learned about the popular Korean culture. Available representations may help an interpretation of the performer starting the Korean drama. The approach used was a qualitative approach with a semiotic studied from peirce.Â There were 3 points of interest in peirce semiotics. Which were icon, index and symbol. The icon portrayed in drakor startup, the shooting site was at the sandbox and the hangang river. Both were known as an iconic sites in South Korea. Then the index seen in the startup film is when seo dal mi was having a religious service as she goes to her car test. Finally, the signed of drakor startup is the festival of chuseok. Further research is recommended for closer analysis so as to provide an even better representation of peirce semiotics analysis.